CSR 2.0 Transforming Corporate Sustainability and Responsibility - Visser, Wayne; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The book examines the evolution and current state of corporate social responsibility (CSR), using a five-stage maturity model: defensive, charitable, promotional, strategic and transformative CSR. The first four stages are dubbed CSR 1.0 and characterise most current CSR practice, while the fifth stage is named CSR 2.0 (also transformative or systemic CSR) and describes emergent and future CSR practices. Reasons are given why CSR 1.0 approaches have failed to have any significant impact on the most serious global social, environmental and ethical challenges. The emergent CSR 2.0 will then be explored in detail by elaborating on five principles underlying the new approach, including: creativity, scalability, responsiveness, glocality and circularity. A four-part DNA Model is also introduced, covering value creation, good governance, societal contribution and ecological integrity, which provides the basis for defining and measuring CSR 2.0. Finally, a 70-question CSR 2.0 self-assessment diagnostic tool developed by the author is presented, with sample data to show how the tool can be used for future research and practitioner application.
Introduction -- Ages and Stages of CSR -- The Failure of CSR 1.0 -- CSR 2.0 as a New Metaphor -- Principles of CSR 2.0 -- Assessing CSR 2.0 Performance -- Conclusion.
Keywords: Economics; Environmental management; Sustainable development; Business planning; Economics/Management Science; Non-Profit Enterprises/Corporate Social Responsibility; Sustainable Development; Organizational Studies, Economic Sociology; Business Strategy/Leadership.; Organization/Planning.; Environmental Management